The anti-fatigue potential of water-soluble polysaccharides of Semen cassiae on BALB/c mice - Kang, Chenzhe; Liu, Yanan; Chi, Aiping; Zhang, Zilin (Cellular and Molecular Biology, 2021)
Fatigue syndrome is a major health problem that affects the voluntary activities of an individual. Particularly, exercise-induced fatigue has become a serious concern in people's health. Since polysaccharides from various medicinal plants have been reported for anti-fatigue effect, the current study deals with the anti-fatigue potential of water-soluble polysaccharides of the Chinese medicinal plant Semen cassiae (Cassia obtusifolia L.) in BALB/c mice. Water-soluble polysaccharides from Semen cassiae were extracted using aqueous solvent (water). An orthogonal test design was employed for the optimization of polysaccharide extraction. The conditions optimized through this design unveiled the raw materials to solvent ratio as 1:30. The optimal temperature and time duration were found to be 80°C and 3.5 h, respectively. The yield of soluble polysaccharides at these specified conditions was 5.42%. Strikingly, the water-soluble polysaccharide from S. cassiae exhibited strong anti-fatigue activity at 100 mg/kg in BALB/c mice. S. cassiae polysaccharide extended the weight-loaded swimming duration in BALB/c mice. In addition, it ameliorated the level of antioxidant enzymes (SOD, GPX) while decreased the blood urea nitrogen, creatine phosphokinase, triglyceride, lactic acid, lactate dehydrogenase, and malondialdehyde levels in blood serum. Moreover, the assessment of the immunomodulatory effect of S. cassia polysaccharides unveiled the enhancement of B-cell and T-cell lymphocytes, denoting the positive effect on physical immunity.